Application of E-Learning Based on Enriched Virtual Model in the Subject Database - Fitria Fitria; Ruslan Ruslan; Muhammad Yusuf Mappeasse (Three E Science Institute, 2021)
The study aims to discover the quality of e-learning based on Enriched Virtual model in database subject in the Computer and Informatics Engineering Study Program uses the ISO/IEC 25010 software quality metric method on the aspects of external quality and quality in use. The development model used in this study was adapted from Borg and Gall development model, consisting of 8 stages, namely, (1) Research and information collecting (initial research and information gathering), (2) Planning, (3) Develop preliminary form of product, (4) Preliminary field testing, (5) Main product revision, (6) Main field testing, (7) Final product revision, and (8) Final product. The subjects in this study were 74 students of Computer and Informatics Engineering Education Study Program. Data were collected through interview, observation, and questionnaire techniques. Data were analyzed using descriptive statistical analysis techniques and software quality metric methods ISO/IEC 25010. Based on the results of the study, e-learning based on Enriched Virtual model is produced in the database subject. The product developed has fulfilled all aspects of development. Media and material validation are in very good category, while the student’s responses are in good category. The results of software quality testing using the quality metric method concludes that the final value of external quality is 0.45 and which is in medium category.